Influence of Waste Oils on the Extracted Aged Binder Properties and Dosage Optimisation - Khan M.Z.H.; Babalghaith A.M.; Koting S.; Ibrahim M.R.; Katman H.Y.B.; Asqool O. (Springer Science and Business Media Deutschland GmbH, 2023)
Asphalt; Oils and fats; Rheology; Aged binder; Asphalt binders; Binder properties; Engine oil; Property; Rejuvenator; Rheological; Rheological property; Waste cooking oil; Waste oil; Binders